'Personal' troubles and public spaces: the community as a site of care and social action. (19th March 2019) - Crean, Mags
Abstract: The crisis in community development in Ireland has been discussed by community workers, academics and equality experts. This article contributes to this analysis with empirical research encompassing the voice of people living with inequality, including a number of community activists. The research shows how affective relations take precedence in women's discussions about social class inequality and activism at a community level. Yet, this everyday concern with the affective is not given a legitimate status in academic and political discourse about community development. It is argued that this depoliticization of affective relations is part of the crisis in community development when it fails to incorporate a political analysis of what matters most to people at a community level.